The Moderating Role of Risk Management Committee Independence in the Relationship between Firm Attributes and Financial Stability of Listed Deposit Money Banks in Nigeria - Babatunde Shamseldeen Ogunjimi; Iyere Samuel Iheonkhan; Naburgi Musa Mohammed (Marasofi International Media and Publishing (MIMP), 2025)
This study investigated how risk management committee independence moderates the relationship between firm attributes and the financial stability of deposit money banks in Nigeria over a ten-year period, from 2014 to 2023. Employing an ex-post facto research design, the study encompassed all 13 deposit money banks listed on the Nigerian Exchange Group, using a census sampling approach due to the manageable population size. Secondary data were extracted from the banks’ annual reports and financial statements. Financial stability, the dependent variable, was measured using the Altman Z-Score, while the independent variables included firm size, profitability, liquidity, and leverage. Risk management committee independence served as the moderating variable. Panel regression analysis was applied, with results indicating that profitability, leverage, and risk management committee independence each have a significant positive effect on financial stability, whereas firm size and liquidity showed no significant impact in the base model. However, when the moderation effect of risk management committee independence was introduced, firm size, profitability, and leverage all exhibited a positive and significant influence on financial stability, while liquidity remained statistically insignificant. The study concludes that risk management committee independence significantly strengthens the effect of firm size, profitability, and leverage on financial stability, though it does not alter the impact of liquidity. It is recommended that deposit money banks in Nigeria enhance governance structures and adopt dynamic risk management practices to improve profitability and financial resilience without hampering growth.